Prevalence of excessive internet use and its correlation with associated psychopathology in 11th and 12th grade students. Issue 2 (20th April 2019) - Kumar, Nitin; Kumar, Arvind; Mahto, Subodh Kumar; Kandpal, Manish; Deshpande, Smita Neelkanth; Tanwar, Parul
Abstract : Background: Globally, the number of internet users has crossed the three-billion mark, while in India users grew over 17% in the first 6 months of 2015 to 354 million. This study presented a background on internet use and the existence of excessive internet use. Aim: To study the extent of internet use in 11th and 12 grade students and the psychopathology, if any, associated with excessive internet use. Methods: 426 students who met the inclusion criteria were recruited from 11th and 12th grade classes from Kendriya Vidyalaya, New Delhi, India, and were assessed by Young's Internet Addiction Test and the Strength and Difficulties Questionnaire. Results: Among the 426 students, the mean internet addiction total score was 36.63 (20.78), which indicated mild level of internet addiction. 1.41% (six students) was diagnosed as excessive internet users, while 30.28% and 23.94% were classified as moderate and mild internet users, respectively. The prevalence of internet addiction between gender was 58.22% in males and 41.78% in females. While both positive (prosocial) and negative (hyperactivity, emotional, conduct and peer problem) impacts of internet use were reported by students, in the current study excessive use of internet had a negative impact on students' lives as compared with positive impact, which was statistically significant ( p <0.0001). Conclusion: Excessive internet use led to abnormal behaviours which cause negative consequences to users. Early diagnosis of risk factors related to excessive internet use, provides education about responsible use and supervision of students by family members.